DAMPAK MEDIA SOSIAL LINE TERHADAP PERILAKU ANTISOSIAL DI KALANGAN REMAJA GUNUNGSARI SURABAYA - Sari, Novie Paramitha; Sudaryanto, Edy; Nasution, Ute Chairus (representamen, 2018)
LINE social media is now widely used by teenagers, the more popular is also thecurrent online media among teenagers. The impact of LINE social media on theseantisocial teenagers also leads to actions that impose physical or psychological damageon others, such as lying, stealing, attacking others, becoming cruel to others, becomingargumentative, and becoming non-discriminating sexually promiscuous.Theories usedare social media theory, antisocial behavior. This research is done by using explanativeresearch method with quantitative method. Sampling technique to be taken for this studyis purposive sampling, the number of samples as many as 60 respondents teenagers whoare domiciled in Gunungsari Surabaya.The result of LINE usage research is media whichhave very strong impact, able to give impact directly to the audience (teenager). Canshake the minds of his audience directly. This term is often used to indicate changes inindividuals caused by exposure to media. With social relationships conducted byindividuals or individuals through social networks as a means of communication tosupport success in achieving goals, then the person will be more often in using socialnetworking media.Keywords: social media applications, antisocial behavior, social media impact